Indigofera leaf meal (ILM) as supplements to increase egg production and quality of Japanese quails - Abdul Rahim, Siti Norain (2016)
Quails egg is considered as a delicacy in many part of the world. Most consumer that concern about their health will take about 2-5 egg per day .The objective of this study was to determine the effect of supplementation of Indigofera leaf meal (ILM) on the production and quality of quail egg. One hundred and twelve ready to lay Cortunix japonica quails, 5 weeks of age, were used in this study. The birds were divided into four treatment groups with four replications with each replicate consisted of seven birds. There were four treatments, namely commercial diet supplemented with ILM at 0% (C0), 0.5 % (T1), 1.0 % (T2) and 1.5 % (T3), respectively. The experiment conducted at Ladang 2 and Nutrition laboratory, in department of Animal Science, University Putra Malaysia. The nutrients content of ILM were crude protein (28.98%), Ash 2.285%, crude fat 3.528%, and crude fibre 8.493%. The birds were allowed 2 week adjustment period followed by the dietary treatments for 4 weeks. Feed intake was determined on a weekly basis. Eggs were collected daily and were evaluated on weight, total production of egg, FCR, yolk index, thickness of shell, colour of yolk and Haugh Unit. Duration for the study is 6 weeks.The total egg production, the weight of the egg and feed conversion ratio were significantly different (p<0.05) among the treatment diets. For the egg quality result, it show that HU is significantly different p (<0.05), yolk index is not significantly different p(>0.05), thickness of the shell is significantly different, and colour also significantly different p(<0.05). In can be concluded that supplemented with the Indigofera leaf meal increased egg production and improved quality in Japanase quail (Cortunix japonica).